Performance analysis of soybean oil with CuO/Graphene hybrid additive nanoparticles as cutting fluid on CNC machining processes - Agus Setiawan; Poppy Puspitasari; Mohammad Tauviqirrahman; Diki Dwi Pramono; Haipan Salam (Universitas Negeri Padang, 2025)
This study investigates the performance of soybean oil-based nano-lubricants with CuO, graphene, and CuO/graphene hybrids under MQL-assisted CNC milling of AISI 1045 steel. The research aims to evaluate the thermophysical, rheological, and tribological properties of various lubricant formulations, including pure soybean oil and soybean oil with individual or hybrid nanoparticle additives. Nanoparticles were characterized by SEM, XRD, and FTIR, and fluid samples were evaluated for density, viscosity, thermal conductivity, sedimentation stability, and rheological behavior. Machining performance was assessed through tool wear, surface roughness, cutting temperature, wear debris morphology, and chip color analysis. Results showed that adding graphene nanoparticles significantly improved machining performance, achieving a surface roughness of 1.033 µm, tool wear of 0.0493 mm, and a cutting temperature of 46.1 °C, outperforming both conventional and alternative nanofluid formulations. Among all formulations, the graphene-based nanofluid delivered the lowest cutting temperature, surface roughness, and flank wear under MQL. The CuO/graphene hybrid improved performance relative to the base fluids but did not surpass the graphene formulation, indicating limited synergistic benefits under the present soybean oil-based-MQL conditions.